Uma proposta de trabalho com o gênero discursivo tiras: enfoque nas questões sociais e culturais - Peres, Gilberto Antonio (2018)
This dissertation is the result of a survey of the Professional Master's Degree in Letters - PROFLETRAS - held at a public school in the state of Minas Gerais with 29 students from the 8th grade. Our theoretical base were mainly the PCN (BRASIL, 1998), Cagnin (2014), Ramos (2016), Vergueiro (2015, 2016). As a methodology, we adopted action research (THIOLLENT, 1986) and the data collection was done from the daily practice book of the participating students as well as the researcher teacher. The data were analyzed in the conception of the qualitative research with interest in the description and the interpretation of them, related to the context in which they are inserted. Our research proposed a work with the discursive genre strips, focusing on social and cultural issues, from a gap found in the Portuguese Language textbooks. We proposed the application of activities in the format of workshops in order to have more integration and interaction between participants in the perception and discussion of social and cultural issues, relating them to the space in which they live. For the elaboration and application of the proposal, we think of two transversal themes (environment and health) and the phenomenon of linguistic variation. The work with the cross-cutting themes made it possible for the students to become more aware of the need for their participation in the social space itself. In reference to the linguistic variation, our purpose was to make the students know that the language is heterogeneous and, from this knowledge, not (more) considered one variety better than another, but that they had capacity to think the language changes in situations of its use. The chosen strips were the characters from the Class of the Xaxado by Antônio Cedraz. In order to focus on the sociolinguistic issue, we are mainly based on Bortoni-Ricardo (2004, 2005), Faraco (2008), Bagno (2007, 2013). With the development of this research, and in accordance with the presented results, we could see that the attitude of the teacher as a researcher gave the participants the search for knowledge in order to demonstrate participation beyond the school space.